Urgensi Mediasi dalam Penyelesaian Sengketa Perceraian Perspektif Hukum Keluarga Islam dan Praktik - Nur, Tarmizi (Penerbit Goodwood, 2024)
Purpose: This study aims to assess the effectiveness of mediation in resolving divorce disputes at the Religious Court, emphasizing its importance to ensure a faster, fairer process aligned with Islamic family law. Research Methodology: The research methodology employed is library research, utilizing scientific journal articles and research reports related to the legal aspects and practices of mediation in divorce. Results: The analysis reveals that: 1) Islamic family law advocates mediation as a suitable mechanism for divorce resolution, promoting family preservation through consultation and consensus based on Sharia law; 2) Mediation practices in Religious Courts face several challenges, including misunderstandings among mediators, resistance from parties, and psychological and social barriers; 3) Mediation is a vital, cost-effective solution that maintains family harmony, reduces the burden on courts, and mitigates social impacts of divorce, necessitating enhanced quality and awareness. Conclusion: Mediation aligns with Sharia principles and is advisable for divorce cases, as it preserves familial ties and facilitates peaceful, expedient resolutions. Limitations: The study is limited to secondary data sources and may not fully represent the current practical challenges faced by mediators in the field. Contribution: This research underscores the need for improved mediation practices within the Religious Court system, advocating for increased awareness and training to optimize its role in family dispute resolution in line with Islamic legal principles.